The (Un)Importance of Inheritance - Sandra E. Black; Paul J. Devereux; Fanny Landaud; Kjell G. Salvanes (Institute of Labor Economics (IZA), 2022)
Transfers from parents-either in the form of gifts or inheritances-have received much attention as a source of inequality. This paper uses administrative data for the population of Norway to examine the share of the Total Inflows (defined as the capitalized sum of net labor income, government transfers, and gifts and inheritances received over the period) accounted for by capitalized gifts and inheritances. We find that gifts and inheritances represent a small share of Total Inflows; this is true across the distribution of Total Inflows, as well as at all levels of net wealth. Gifts and inheritances are only an important source of income flows among those who have very wealthy parents. Additionally, gifts and inheritances have very little effect on the distribution of Total Inflows, suggesting that inheritance taxes may do little to mitigate wealth inequality.
Keywords: G51; J01; J1; 330; intergenerational transmission; inheritances and gifts; wealth inequality